2016
DOI: 10.1123/jpah.2016-0314
|View full text |Cite
|
Sign up to set email alerts
|

Results From Chile’s 2016 Report Card on Physical Activity for Children and Youth

Abstract: Background:The 2016 Chilean Report Card on Physical Activity for Children and Youth is a review of the evidence across indicators of behaviors, settings, and sources of influence associated with physical activity (PA) of Chilean children and youth.Methods:A Research Work Group reviewed available evidence from publications, surveys, government documents and datasets to assign a grade for 11 indicators for PA behavior based on the percentage of compliance for defined benchmarks. Grades were defined as follows: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 26 publications
0
25
0
6
Order By: Relevance
“…In Chile's first Report Card (2016), all indicators had low grades, and data from different surveys indicated that there were consistent disparities across genders, socioeconomic status, and school types. 67 In 2018, Chile's grades remained low in comparison with the first Report Card in 2016 but progress was made on environmental and policy aspects, 68 raising hope that these improvements will positively affect behavioral indicators in the future.…”
Section: Least Successful Countriesmentioning
confidence: 99%
“…In Chile's first Report Card (2016), all indicators had low grades, and data from different surveys indicated that there were consistent disparities across genders, socioeconomic status, and school types. 67 In 2018, Chile's grades remained low in comparison with the first Report Card in 2016 but progress was made on environmental and policy aspects, 68 raising hope that these improvements will positively affect behavioral indicators in the future.…”
Section: Least Successful Countriesmentioning
confidence: 99%
“…Chile's first Report Card (RC) on Physical Activity for Children and Youth released in 2016 graded with an F overall physical activity (PA), as only 3 out of 10 children and 2 out of 10 youth performed at least 60 minutes of moderate-to vigorous-intensity PA per day. 1 Most indicators received very low grades, except for Community and Environment, and Government Strategies and Investments. In the present study, we aimed to summarize the results of the Chile's second RC for 13 PA-related indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the success achieved in Slovenia suggests that behavioral changes associated with such transitions are not inevitable. Canada, 27 Denmark, 31 the Netherlands, 44 Sweden 55 ), whereas countries with low grades for Organized Sport Participation often reported low grades for School and Community and the Built Environment (eg, Chile, 28 Mexico, 42 Mozambique 43 )]. This relationship was significant (Spearman's rho for Organized Sport Participation grade ~ School + Community and Environment grades = 0.42, P = .02) and is not surprising considering that organized sport opportunities require space, facilities, equipment, programs, safety precautions, and supervision.…”
Section: Successes and Challenges Based On Indicator Gradesmentioning
confidence: 99%